Merangkai Arena Menuai Kuasa: Romantika Dan Perjuangan Group Musik Dangdut Hip-Hop NDX A.K.A Yogyakarta - Edy Purwanto (Journal of Social, Culture, and Language, 2023)
The music industry flourished in the late modern era especially for some of the concerts and the crowded nightclub. The music industry has always brought joy to people around the world. But behind that, there was a battle, rivalry and competition. While artists compete to reach the top of the charts and gain popularity, record companies struggle to find and nurture new talent. Still quite hesitant, the music industry has always provided opportunities for talented and dedicated people to pursue their dreams. NDX, aka Yogyakarta Group Music, is no exception. This study explores how NDX AKA creates symbolic capital, manages the reproduction of capital, and expands the battlefield using qualitative descriptive methods with Pierre Bourdieu's practical theory approach . Data for this study were obtained from interviews and field observations. After going through a data analysis process, researcher found that NDX AKA, also known as group music, constitutes its musical habits from an accumulation of cultural capital derived from the family and social environment that created the ethos of working in the music industry. NDX Group hopes to deploy a transformational strategy by diversifying cultural capital of business and fashion products into economic.Keywords: DIY, Pierre Bourdieu, NDX AKA